AI Doc Helper - Kothavale, Ranveer; Ekbote, Archana P. (Indian Journal of Computer Science, 2022)
For numerous times, numerous people have failed due to undetected conditions. Early discovery of these conditions at the micro bracket stage can be useful for furnishing proper treatment of the cases at an early stage and could have saved a lot of lives. A lot of exploration is being done to describe these conditions at the foremost. Thus, a computer-backed or Artificial Intelligence approach for detecting conditions at the early stage is being proposed, which makes use of machine, literacy and deep literacy algorithms for detecting conditions. This system will describe all general conditions similar to different types of cancer, malaria, diabetic retinopathy, etc. AI-Doc Helper is being proposed as there's no system available that detects all these general conditions.